Identification of 17 highly expressed genes within mouse lumbar spinal cord anterior horn region from an in-situ hybridization atlas of 3430 genes: implications for motor neuron disease - Michael A. Meyer (MDPI AG, 2014)
In an effort to find possible new gene candidates involved in the causation of amyotrophic lateral sclerosis (ALS), a prior version of the on-line brain gene expression atlas GENSAT was extensively searched for selectively intense expression within spinal motor neurons. Using autoradiographic data of in-situ hybridization from 3430 genes, a search for selectively intense activity was made for the anterior horn region of murine lumbar spinal cord sectioned in the axial plane. Of 3430 genes, a group of 17 genes was found to be highly expressed within the anterior horn suggesting localization to its primary cellular constituent, the alpha spinal motor neuron. For some genes, an inter-relationship to ALS was already known, such as for heavy, medium, and light neurofilaments, and peripherin. Other genes identified include: Gamma Synuclein, GDNF, SEMA3A, Extended Synaptotagmin-like protein 1, LYNX1, HSPA12a, Cadherin 22, PRKACA, TPPP3 as well as Choline Acetyltransferase, Janus Kinase 1, and the Motor Neuron and Pancreas Homeobox 1. Based on this study, Fibroblast Growth Factor 1 was found to have a particularly selective and intense localization pattern to the ventral horn and may be a good target for development of motor neuron disease therapies; further research is needed.